Detecting neuronal dysfunction of hand motor cortex in ALS: A MRSI study. (2nd January 2017) - Wang, Yuzhou; Li, Xiaodi; Chen, Wenming; Wang, Zhanhang; Xu, Yan; Luo, Jingpan; Lin, Hanbo; Sun, Guijun
Abstract: Background: Although hand motor cortex (HMC) has been constantly used for identification of primary motor cortex in magnetic resonance spectroscopy (MRS) studies of amyotrophic lateral sclerosis (ALS), neurochemical profiles of HMC have never been assessed independently. As HMC has a constant location and the clinic–anatomic correlation between hand motor function and HMC has been established, we hypothesize that HMC may serve as a promising region of interest in diagnosing ALS. Patients and methods: Fourteen ALS patients and 14 age- and gender-matched healthy controls (HC) were recruited in this study. An optimized magnetic resonance spectroscopic imaging (MRSI) method was developed and for each subject bilateral HMC areas were scanned separately (two-dimensional multi-voxel MRSI, voxel size 0.56 cm 3 ). N-acetyl aspartate (NAA)–creatine (Cr) ratio was measured from HMC and the adjacent postcentral gyrus. Results: Compared with HC, NAA/Cr ratios from HMC and the postcentral gyrus were significantly reduced in ALS. However, in each group the difference of NAA/Cr ratios between HMC and the postcentral gyrus was not significant. Limb predominance of HMC was not found in either ALS or HC. In ALS, there was a significant difference in NAA/Cr ratio between the most affected HMC and the less affected HMC. A positive relationship between NAA/Cr ratio of HMC and the severity of hand strength (assessed by finger tapping speed) was demonstrated. Conclusion: Neuronal dysfunction of HMC can differentiate ALS patients from HC when represented as reduced NAA/Cr ratio. Postcentral gyrus could not serve as normal internal reference tissue in diagnosing ALS. Asymmetrical NAA/Cr ratios from bilateral HMC may serve as a promising diagnostic biomarker of ALS at the individual level.